Integrated Omics Reveals the Orchestrating Role of Calycosin in Danggui Buxue Tang, a Herbal Formula Containing Angelicae Sinensis Radix and Astragali Radix, in Inducing Osteoblastic Differentiation and Proliferation - Kenneth K L Kwan; Kenneth K L Kwan; Tin Yan Wong; Anna X D Yu; Anna X D Yu; Tina T X Dong; Tina T X Dong; Henry H N Lam; Karl W K Tsim; Karl W K Tsim (Frontiers Media S.A., 2021)
Systems biology unravels the black box of signaling pathway of cells; but which has not been extensively applied to reveal the mechanistic synergy of a herbal formula. The therapeutic efficacies of a herbal formula having multi-target, multi-function and multi-pathway are the niches of traditional Chinese medicine (TCM). Here, we reported an integrated omics approach, coupled with the knockout of an active compound, to measure the regulation of cellular signaling, as to reveal the landscape in cultured rat osteoblasts having synergistic pharmacological efficacy of Danggui Buxue Tang (DBT), a Chinese herbal formula containing Angelicae Sinensis Radix and Astragali Radix. The changes in signaling pathways responsible for energy metabolism, RNA metabolism and protein metabolism showed distinct features between DBT and calycosin-depleted DBT. Here, our results show that calycosin within DBT can orchestrate the osteoblastic functions and signaling pathways of the entire herbal formula. This finding reveals the harmony of herbal medicine in pharmacological functions, as well as the design of drug/herbal medicine formulation. The integration of systems biology can provide novel and essential insights into the synergistic property of a herbal formula, which is a key in modernizing TCM.